The Determinants Of The Composite Stock Price Index (CSPI) On The Indonesia Stock Exchange (IDX) Based On The Straits Times Index (STI), Brent Crude Oil Price, And Exchange Rate Of The US Dollar During The Period Of 2019-2023 - Selfi Nasrul Rosydha; Jojok Dwiridotjahjono (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The capital market plays a crucial role in a country's economy, where the Composite Stock Price Index (IHSG) serves as a primary indicator for measuring the performance of the stock market in Indonesia. This study aims to analyze the influence of the Straits Times Index (STI), Brent Crude Oil Prices, and the Exchange Rate of the US Dollar on the IHSG at the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The research employs a quantitative approach with an associative research type. The data used is secondary data obtained from relevant sources. The research sample consists of 60 monthly data points covering the STI, Brent Crude Oil Prices, and the Exchange Rate of the US Dollar. Data analysis is conducted using multiple linear regression with classical assumption tests to ensure the validity of the research model. The results indicate that, simultaneously, the variables STI, Brent Crude Oil Prices, and the Exchange Rate of the US Dollar significantly affect the IHSG. Partially, STI and Brent Crude Oil Prices have a positive and significant impact on the IHSG, while the Exchange Rate of the US Dollar has a negative impact. An increase in STI and Brent Crude Oil Prices drives the IHSG higher, whereas a depreciation of the rupiah against the US dollar contributes to a decline in the IHSG. This study provides insights for investors and relevant stakeholders in understanding the external and internal factors influencing the IHSG and can serve as a reference for investment decision-making.